Pola Tanam Usahatani dan Nilai Ekonomi Air pada Kecamatan Lumajang - Hasan, Ilham; Rondhi, Mohammad; Aji, Joni Murti Mulyo (Universitas Galuh, 2025)
Water is the most important part in cultivating plants, the availability of water is a source of agricultural support so that agricultural plants grow optimally. However, there is a scarcity of water supply in Lumajang sub-district, to meet the water needs of the land, farmers have built pump wells to distribute water to the land to meet the needs of rice and corn crops. This needs to be taken into account due to high operational costs, so calculating the economic value of pump well irrigation water is important. Researcher's objectives (1) What is the economic value of pump well model irrigation water. (2) What factors influence the economic value of pump well model irrigation water. The research area chosen by Lumajang District was carried out using the method Purposive sampling and methods Proportionate Stratifield Random Sampling. Research Methods use descriptive and quantitative methods. Analytical tools use analytics Residual Imputation Approach (RIA) and Multiple Linear Regression analysis. The results of the RIA analysis of the economic value of pump model irrigation water in the dry season are the value of water in these 3 areas for cultivating corn and rice plants, in the dry season the operational costs for irrigating rice plants have a high volume of water, so farmers use water efficiently. Multiple linear regression analysis of factors influencing the economic value of pump irrigation water, Education (X1) has a significant effect with a coefficient of - 242.837, has a real negative effect on the economic value of pump irrigation water, and total income (X2) has a significant effect with a coefficient of 0.175, meaning it has a real positive influence on the economic value of pump irrigation water